#TITLE_ALTERNATIVE# - AZRIEL SIDDIK (NIM : 13205098), GERI
This final project uses a simulation tool to analyze the performance of the IEEE 802.11b ad hoc network. The ad hoc network has a wide variety of applications but is more prominent in decentralized networks lacking pre-existing infrastructure such as in dynamic tactical situations. The simulation scenarios comprised two 802.11b ad hoc network topology models. One was a line model consisting of 16 nodes and the other was a grid model with 25 nodes. Both had AODV routing protocols with TCP and UDP 1400 Byte traffic data. The variations in topology types, data connection types and increases in the amounts of hops and nodes were the variables in these simulations. The ad hoc simulations were carried out using the National Chiao Tung University Network Simulator (NCTUns). The parameters observed in the simulations include routing, delay, packet loss, delivery packet ratio and throughput. The results of the simulation revealed that the amount of hop in the network led to a decrease in performance of the ad hoc network. Furthermore, TCP connections were also found to decrease throughput in the network's receiving node.